2008
DOI: 10.1080/14786430802235804
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection arrays in a rhombohedral twin in α-alumina

Abstract: International audienceInterfacial defects such as grain boundary dislocations are known to play an important role in the creep behavior of alumina. In the present work interfacial defects are analyzed in detail using a Volterra approach without a reference to a near-coincidence description. We investigate disconnections (boundary steps with dislocation character) in a diffusion-bonded alumina bicrystal with a misorientation close to the rhombohedral twin by conventional and atomic resolution electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The screw components (parallel to the [0 0 1] axis) of two close dislocations should be opposite so as to cancel long-range stress fields. Such distributions of dislocations with opposite screw components have been found for intergranular disconnections [38]. Also, the components normal to the interface plane are expected to annihilate if the ð1 0 1 0Þ TiB 2 and (1 0 0) Fe planes are strictly parallel.…”
Section: Interface Parallel To a Prismatic Planementioning
confidence: 92%
“…The screw components (parallel to the [0 0 1] axis) of two close dislocations should be opposite so as to cancel long-range stress fields. Such distributions of dislocations with opposite screw components have been found for intergranular disconnections [38]. Also, the components normal to the interface plane are expected to annihilate if the ð1 0 1 0Þ TiB 2 and (1 0 0) Fe planes are strictly parallel.…”
Section: Interface Parallel To a Prismatic Planementioning
confidence: 92%
“…In alumina, the bicrystal method, joining two pieces of single crystal at high temperature, is useful to obtain well-oriented grain boundaries [18][19][20]. So far, we have systematically fabricated alumina bicrystals with a low-angle grain boundary and characterized the dislocation structures formed in the grain boundaries by TEM [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Dislocation networks within GBs are difficult to study experimentally. However, some recent experimental work using TEM has been reported [68][69][70][71]. Hong et al observed networks of perfect dislocations (Burger's vector 〈110〉/2) in boundaries with small inclination to {111} planes in rolled Al [20].…”
Section: Discussionmentioning
confidence: 99%